Stereotactic radiosurgery and combined immune checkpoint therapy with ipilimumab and nivolumab in patients with melanoma brain metastases: A retrospective monocentric toxicity analysis - Bodensohn, Raphael; Werner, Simone; Reis, Jonas; Pazos Escudero, Montserrat; Kaempfel, Anna Lena; Hadi, Indrawati; Forbrig, Robert; Manapov, Farkhad; Corradini, Stefanie; Belka, Claus; Theurich, Sebastian; Heinzerling, Lucie; et al. (Clinical and Translational Radiation Oncology, 2023)
Purpose and objective: Adding stereotactic radiosurgery (SRS) to combined immune checkpoint therapy with ipilimumab and nivolumab (IPI + NIVO) has led to promising results for patients with melanoma brain metastases (MBM). This study retrospectively analyzes the toxicity profile depending on the timing of SRS with regard to IPI + NIVO. Materials and methods: For this study, the clinical database was searched for all patients with MBM who were treated with SRS and IPI + NIVO. The patients were separated into three groups: group A completed IPI + NIVO (usually up to four cycles) >14 days before SRS, in group B IPI + NIVO was initiated>14 days after SRS, and group C received SRS concurrently to IPI + NIVO. Treatment related toxicity was obtained from clinical and neuroradiological records. Analyses were performed using the Fisher-Yates-test. Results: 31 patients were assessed including six (19.4 %), seven (22.6 %) and 18 (58.1 %) patients, in groups A, B and C, respectively. Baseline prognostic markers between groups were balanced. In total, five (16.1 %) patients experienced neurological grade 3 toxicities related to SRS. All of these five patients were in group C, which was near-significantly correlated with a risk for grade 3 toxicities (p = 0.058). Post-hoc analyses showed that a maximum time period of seven days between SRS and IPI + NIVO was significantly correlated with grade 3 toxicity (p = 0.048). Conclusion: Application of SRS to IPI + NIVO within a seven-day span was related to higher toxicity rates in this retrospective analysis. After previous studies focused on immune checkpoint monotherapies with SRS and declared it as safe, this study indicates that concomitant application of IPI + NIVO and SRS might increase side effects. Prospective validation is warranted to corroborate these findings.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Checkpoint inhibition; Intracranial hemorrhage; Ipilimumab; Nivolumab; Radiation necrosis; Side effects; Stereotactic radiosurgery